2023
DOI: 10.3390/admsci13030081
|View full text |Cite
|
Sign up to set email alerts
|

Bolstering the Moderating Effect of Supervisory Innovative Support on Organisational Learning and Employees’ Engagement

Abstract: Organisational learning, as the process of continuous information acquisition, dissemination and exploitation, often leads to an organisation’s competitiveness. Hence, this study examined the relationship between organisational learning and employee engagement. The study also investigated the extent to which supervisory innovative support moderates organisational learning and the effectiveness of employee engagement. Five hundred forty-one (541) participants were surveyed using stratified and purposive samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Additionally, it explains why employees are willing to exceed the requirements of their job descriptions. According to Opeyemi et al [14] behavioural engagement signifies employees' ability to adapt to new situations, their intentions to learn and acquire new skills and their ability to maintain their energy and alertness within the organization.…”
Section: Behavioural Engagementmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, it explains why employees are willing to exceed the requirements of their job descriptions. According to Opeyemi et al [14] behavioural engagement signifies employees' ability to adapt to new situations, their intentions to learn and acquire new skills and their ability to maintain their energy and alertness within the organization.…”
Section: Behavioural Engagementmentioning
confidence: 99%
“…Jani et al [13] also define cognitive engagement as the degree to which employees are mentally conscious of their roles while keeping the organization's objectives in mind. Opeyemi et al [14] affirm that when employees possess a sustainable, gratifying and positive mindset, they are cognitively engaged. Existing studies suggest that employee cognitive engagement is higher in organizations that efficiently and effectively distribute information [12].…”
Section: Cognitive Engagementmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Chen and Silverthorne (2005), Romão et al (2022), Yücel (2021), andVinh et al (2022) leadership style can positively affect job satisfaction, which in turn positively affects organizational commitment and job performance. Irshad and Afridi (2007), Joel et al (2023) and Zayed et al (2022) found that if superiors support their subordinates, communicate openly, and maintain good relationships with them, employees' turnover intentions will decrease. Alblooshi et al (2021) draw attention to the fact that the organization must employ managers who support employees and create a work environment in which employees are happy to work.…”
Section: Supervisionmentioning
confidence: 99%